Toward more equal and mutual human-pet relations: Insights and possible solutions based on social psychological theories - Amiot, Catherine E.; Santerre-Bélec, Laurence (Frontiers in Veterinary Science, 2022)
Human-pet relations are imbued with power imbalances, with many pets depending on humans for food and water, shelter, health care, and sheer survival. A majority of people report loving their pets and consider them to be integral family members; however, the care provided to pets varies widely and can be, in some cases, suboptimal. Yet, building more equal relations between humans and their pets could provide benefits to both parties. To achieve this increased equality and mutuality, the current paper proposes theory-based solutions. Specifically, and building on established social psychological theories, namely theories of intergroup relations and of human motivation, the current paper identifies both social and relational factors which, if socially and individually promoted, could trigger more equal and possibly mutually beneficial relationships with pets. We provide concrete examples illustrating how these factors can be maximized and promoted.